Arch replacement using antegrade selective cerebral perfusion for shaggy aorta. (February 2013) - Takagi, Yasushi; Ando, Motomi; Akita, Kiyotoshi; Ishida, Michiko; Kaneko, Kan; Sato, Masato
Background: Embolic stroke during arch replacement is a serious concern in patients with shaggy aorta. Objective: To evaluate shaggy aorta in patients who received total aortic arch replacement with antegrade selective cerebral perfusion utilizing axillary perfusion. Method: Between January 2005 and December 2010, 63 patients underwent preoperative contrast-enhanced computed tomography scanning of the aorta to evaluate atheromatous plaque. We analyzed operative data to investigate which factors were associated with outcomes and survival. Results: Shaggy aorta was found in 34 (54%) patients. There were 3 (5%) cases in the ascending aorta, 26 (41%) in the aortic arch, and 19 (30%) in the descending aorta. Operative mortality occurred in 1 (2%) patient. Although stroke occurred in 2 (3%) shaggy aorta patients, shaggy aorta was not associated with an increased likelihood of stroke ( p = 0.4951). Survival was significantly lower in patients with shaggy descending aorta ( p = 0.0411) and in patients >75-years old ( p = 0.0200); these traits were identified as independent risk factors for late death ( p = 0.0368 and p = 0.0100, respectively). Conclusion: We concluded that our perfusion technique protects patients with shaggy aorta against embolism, and that the survival is lower in patients with shaggy descending aorta.